Efficacy of Negative-Pressure Wound Therapy with Tetrachlorodecaoxygen-Anion Complex Instillation Compared with Standard Negative-Pressure Wound Therapy for Accelerated Wound Healing: A Prospective, Randomized, Controlled Trial. Issue 2 (21st June 2021) - Burusapat, Chairat; Sringkarawat, Sophilak
Abstract : Background: Negative-pressure wound therapy (NPWT) with instillation is a novel wound therapy. The optimal solution is still being investigated. Tetrachlorodecaoxygen-anion complex (TCDO) causes increased phagocytosis and oxygenation. The authors' objective was to investigate the efficacy of NPWT with TCDO instillation (NPWTi) and to compare the results with NPWT alone. Methods: A randomized controlled trial was conducted. Inclusion criteria were wound size greater than 4 cm 2 and depth greater than 10 mm. Exclusion criteria were malignancy, immunocompromise, and allergy to TCDO. Patients were randomized into NPWT and NPWTi groups. Outcome measurements consisted of wound surface area, depth, volume, tissue culture, and pathologic evaluation. Results: A total of 24 patients in each group were enrolled. The percentages of wound surface area reduction of NPWTi and NPWT groups were 24.1 ± 6.8 and 28.2 ± 7.6 on day 12, and 19.0 ± 6.6 and 22.7 ± 7.8 on day 15, respectively ( p < 0.05). The percentages of wound depth reduction were 16.4 ± 5.3 and 22.5 ± 10.5 on day 12, and 12.0 ± 6.7 and 14.1 ± 8.0 on day 15, respectively ( p < 0.05). The percentages of wound volume reduction were 17.9 ± 4.6 and 21.6 ± 5.8 on day 12, and 14.7 ± 6.0 and 17.1 ± 6.6 on day 15, respectively ( p < 0.05). No statistically significant difference in microbial reduction was found between the groups. Histopathologic examination showed that more angiogenesis was observed in the NPWTi group than in the NPWT group. Conclusions: NPWT with TCDO instillation statistically significantly accelerated wound healing, but it did not show significant microbial reduction. The authors' results suggest that TCDO instillation may be an adjunctive treatment in NPWT. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.